Barriers to Reproductive Health Services Among Female Youths of Suklagandaki Municipality in Western Part of Nepal - Thapa, Asha; Yadav, Dipendra Kumar; Shrestha, Jene; Shah, Jay Prakash (Journal of Karnali Academy of Health Sciences, 2021)
Background: Youths have specific sexual health needs, which vary according to their age, sex, marital and socioeconomic status. Although sexual and reproductive health education and services are provided to young people, unplanned pregnancy and HIV infection are increasing in Nepal, indicating underutilization of sexual health services by young people. The study aimed to explore the barriers to reproductive health services among female youths of Suklagandaki Municipality, Nepal. Methods: A qualitative study was conducted through in-depth interviews among female youths aged 14 to 25 and two focus group discussions among FCHVs and health workers in health post. Snowball sampling technique was used for the selection of participants for in-depth interview. Results: The barriers identified were poor sexual health knowledge, fear and embarrassment, poor youth friendly health services, misconceptions regarding contraceptives and negligence about the problems. Conclusions: Prejudice regarding utilization of reproductive health services by youths has been identified a major contributing factor or barrier, which requires integrated effort from all sector to tackle this barrier. Awareness programs focusing reproductive health services and its importance should be conducted in various places targeting the different groups along with youths to normalize the concept of reproductive health among all. The integrated effort of school, community, and health facilities are important for encouraging utilization of reproductive health facilities among youths